EVALUASI PROGRAM KURSUS CALON PENGANTIN (SUSCATIN) PASCA PANDEMI DI KUA UJUNGPANGKAH GRESIK - Albaar, Ragwan; Amriana, Amriana (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The Premarital Course Program (Suscatin) is a strategic government initiative aimed at preparing young couples for a mature and responsible marriage life. This study aims to evaluate the implementation of the Suscatin program after the Covid-19 pandemic at the Office of Religious Affairs (KUA) in Ujungpangkah District, Gresik Regency, using the CIPP (Context, Input, Process, Product) evaluation model. A descriptive qualitative method was applied, with data collected through observation, in-depth interviews, and documentation. The findings indicate that contextually the program aligns with community needs and government regulations. However, in its implementation, the program faces several challenges, including insufficient duration (only 4 hours, below the national standard), limited use of interactive teaching methods, and the absence of formal evaluation and follow-up mechanisms. The program also lacks deep integration of Islamic spiritual values. Nevertheless, Suscatin has improved participants’ basic knowledge of marital rights and responsibilities, reproductive health, and family psychology. This study recommends extending the program duration, enhancing interactive methods, conducting regular evaluations, and integrating Islamic values to optimize the program’s role in fostering sakinah, mawaddah, wa rahmah families.